Lean-Season Food Transfers Affect Children's Diets and Household Food Security: Evidence from a Quasi-Experiment in Malawi. Issue 5 (5th April 2017) - Gelli, Aulo; Aberman, Noora-Lisa; Margolies, Amy; Santacroce, Marco; Baulch, Bob; Chirwa, Ephraim
Abstract: Background: There is evidence that social transfers increase food consumption, improving the quantity and quality of food consumed by poor households. Questions remain on how to improve the effectiveness of social programs. Objective: The aim was to assess the impact of a lean-season food transfer on household food security, diet, and nutrition status of young children during the lean season in Malawi and to understand processes through which transfers operated. Methods: This was a longitudinal, quasi-experimental study based on 2 survey rounds in the Zomba district in Malawi. Data were collected from 60 communities randomly selected among food-insecure villages. Twenty households were randomly selected for interviews within each community. Study outcomes included household expenditures and food consumption (measured by using 7-d recall) and child-level dietary diversity (measured by using 24-h recall) and nutritional status (anthropometric measurements). We followed a mixed-methods approach involving child- and household-level assessments, as well as interviews with community stakeholders. We estimated program impact by combining propensity score matching and difference-in-difference methods. Results: The per capita effect of food transfers on food expenditure was estimated at 36 Malawian kwachas/d, corresponding to an increase of 19% from baseline. There was evidence of increased iron availability in household intake. Highly significant effects were found on children's dietary diversity score, corresponding to an increase of 15%, as well as a positive effect on weight-for-height z scores (WHZs) of >0.25 SDs. Effects on food expenditure and dietary diversity were robust to alternative matching specifications, although the effect on WHZs was not. Examination of the targeting of the transfer showed evidence of large errors of inclusion and exclusion. Conclusion: During the lean season in food-insecure settings, where important declines in food insecurity, diet quality, and nutrition status are present, food transfers may have a protective effect on household food security and diets of young children.